Implementation of the Attributed Authority of the Bengkulu Provincial Environmental Agency (DLHK) in the Legal Protection of Rafflesia arnoldii as an Endemic Flora - Varik Farsyak; Ridho Saputra; Ema Septaria; Edra Satmaidi; Muhammad Syirazi Neyasyah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the position and limits of the attribution authority of the Environment and Forestry Service (DLHK) of Bengkulu Province in protecting Rafflesia arnoldii as an endemic flora, and to assess the effectiveness of the implementation of legal protection instruments in addressing the threat of habitat destruction and illegal exploitation. The research method used is normative juridical with a legislative and conceptual approach, supported by limited empirical data through literature study. The results show that DLHK has strong and independent attribution authority based on the Law on Conservation of Biological Natural Resources and the Law on Regional Government, with the scope of regulatory, supervisory, law enforcement, and coordination functions. However, the implementation of legal protection for Rafflesia arnoldii has not been optimal. This is due to the high level of habitat destruction due to human activities, the persistence of illegal exploitation, limited institutional resources, and weak supervision and law enforcement. In addition, low public awareness also exacerbates this condition. Therefore, more comprehensive efforts are needed through strengthening institutional capacity, improving law enforcement, sustainable habitat protection, and community involvement in conservation activities. Thus, it is hoped that protection of Rafflesia arnoldii can be more effective and sustainable.